Using Propagules to Restore Coastal Marine Ecosystems - Vanderklift, Mathew A.; Doropoulos, Christopher; Gorman, Daniel; Leal, Inês; Minne, Antoine J. P.; Statton, John; Steven, Andrew D. L.; Wernberg, Thomas (Frontiers in Marine Science, 2020)
Reversing the decline of coastal marine ecosystems will rely extensively on ecological restoration. This will in turn rely on ensuring adequate supply and survival of propagules — for the main habitat-forming taxa of coastal marine ecosystems these are mainly fruits, seeds, viviparous seedlings, zoospores or larvae. The likelihood of propagule survival — and so restoration success — depends on species- and context-specific knowledge to guide choices about appropriate methods to use. Here, we briefly review life-histories of the main habitat-forming taxa of six coastal marine ecosystems: mangrove forests, tidal marshes, seagrass meadows, kelp forests, coral reefs and bivalve reefs. Restoration of several of these ecosystems has long harnessed the unique properties of propagules, sometimes because they are simple to use (for example, planting propagules of some mangroves), and sometimes because we can draw on knowledge gained from other applications (for example using knowledge of oyster culture to restore bivalve reefs). For other ecosystems, like seagrass meadows, kelp forests and coral reefs, propagules have not yet been widely used, but there is compelling evidence that they can be. Most restoration efforts have used relatively simple techniques, such as manual collection and direct planting or seeding. Some approaches use more complex techniques which include a stage in which propagules are reared in nurseries or aquaria to a size or age at which they are viable, when they are then planted or released at the site to be restored. Other approaches use minimal intervention, and focus instead on providing the conditions that will promote growth from naturally-dispersed propagules (such as restoring hydrological conditions to facilitate mangrove recruitment). Future approaches could incorporate knowledge applied from other fields, such as genetics and agriculture, and harness the possibilities provided by technology. Understanding the importance of propagule quality will likely also yield insights, as will effective use of models to help refine restoration methods for testing. Deeper partnerships between practitioners and researchers will help test and develop better methods so that we can learn from each other and strive to improve. Propagules offer multiple promising avenues to expand coastal marine restoration efforts and help achieve global ambitions.